Optimizing Fiqh Learning Based on the Book of Nadẓam Safinatu Al-Najah by Sheikh Hasan Genggong to Improve the Worship Competence of MI Nidhamiyah Ketompen Students - Isnainiyah Isnainiyah; Ainur Rofiq Sofa (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study aims to find out how the optimization of fiqh learning based on the book of Nadẓam Safinatu al-Najah by Sheikh Hasan Genggong can improve the worship competence of MI Nidhamiyah Ketompen students. The research used a descriptive qualitative method with a field study approach, involving 20 6th grade students as the focus of the research. Data was collected through learning observations, interviews with teachers and vice principals, as well as documentation of student records and books used. The results of the study show that the implementation of learning based on the book of nadẓam is carried out in a systematic, interactive, and fun manner. Students actively read, copy, interpret, and practice worship ordinances, so that their understanding of worship theory and practice increases significantly. Students' worship competencies before the application of the book of nadẓam vary, with some students still having difficulty in practicing ablution, prayer, and taharah. After application, students are more confident, consistent in carrying out daily worship, and are able to memorize and understand nadẓam verses well. Factors that support the effectiveness of learning include teacher and student motivation, the availability of books, interactive methods, and a conducive madrasah environment. The obstacles that arise are differences in reading ability, limited study time, and the need for additional guidance for certain students. This research shows that fiqh learning based on the book of nadẓam is effective in improving worship competence, shaping students' religious character, and preserving the classical literature of the Ganggong Islamic Boarding School.